Rules and Scorecard Grading Policies for the Annual Florida 4-H/FFA Land Judging Contest - Amy L. Shober; L. Rex Ellis; Christine Wiese; Edward A. Hanlon; Randy B. Brown; J. H. Herbert (EDIS, 2011)
This revised 11-page fact sheet outlines the rules of the annual Florida 4-H/FFA Land Judging Contest and guides participants in correctly completing the Land Judging and Homesite Evaluation scorecards. Written by Amy L. Shober, L. Rex Ellis, Christine Wiese, Edward A. Hanlon, Randy B. Brown, and J.H. Herbert, Jr., and published by the UF Department of Soil and Water Science, November 2011.